KETERAMPILAN TEKNIK DASAR SERVIS, LOB DAN SMASH BULU TANGKIS PADA EKSTRAKURIKULER DI SMP NEGERI 18 PONTIANAK - Remi Akbar; Fitriana Puspa Hidasari; Mimi Haetami (Universitas Tanjungpura, 2020)
AbstractThe problem taken in this study is that there are many badminton extracurricular enthusiasts, but lack of achievement. Badminton training is done twice a week, but basic technical skills are not yet maximal. The lack of events was held as a general evaluation and routine exercises. Based on the problems of this study aims to determine the basic technical skills of long service, short service, lob, and badminton smash on extracurricular at SMP Negeri 18 Ponntianak. The method taken in this study is a survey method to get data from a particular place. The population in this study were students who participated in badminton extracurricular activities by 20 students. Based on the results of the study of the item test data used from 20 students who took part in extracurricular badminton books at SMP Negeri 18 Pontianak received an average value of 59.88% which was included in the ENOUGH category. Keywords: Basic Technical Skills Of Badminton